Static and Dynamic Precipitation Behavior of the Al–20wt.% Zn Alloy*Supported by the National Basic Research Program of China under Grant No 2013CB733000, the Natural Science Foundation of Guangxi Province under Grant No 2015GXNSFBA139238, and the Guangxi 'Bagui' Teams for Innovation and Research. (May 2016) - Liu 刘, Chong-Yu 崇宇; Jiang 江, Hong-Jie 鸿杰; Wang 王, Chun-Xia 春霞; Qi 亓, Hai-Quan 海全; Li 李, Yi-Bing 义兵; Ma 马, Ming-Zhen 明臻; Liu 刘, Ri-Ping 日平
Abstract : The static and dynamic precipitation behavior of solution-treated binary Al–20 wt.% Zn alloy is investigated via artificial aging, cold rolling and artificial aging combined with cold rolling. The solution-treated Al–Zn alloy exhibits high thermal stability during aging, and low densities of nano-sized Zn particles are precipitated along with Al grain boundaries after aging at 200°C for 13 h. Compared with static precipitation, dynamic precipitation occurs more easily in the Al–Zn alloy. Zn clusters are obtained after cold rolling at an equivalent plastic strain of 0.6, and the size of the Zn phase reaches hundreds of nanometers when the strain is increased to 12.1. The results show that the speed of static precipitation can be significantly enhanced after the application of 2.9 rolling strain. Grain refinement and defects induced by cold rolling are considered to promote Zn precipitation. The hardness of Al–Zn alloy is also affected by static and dynamic precipitations.